Implementasi Wakaf Produktif untuk Meningkatkan Kesejahteraan Masyarakat - Lisda Aisyah; Agus Alimuddin; Bambang Suhada (Ecoplan, 2020)
Abstract-Waqf is one of the worships performed by separating personal property into used and utilized in general. Waqf property will be used for the needs of Muslims and the general public. The jurist, The Waqf that continues to be used, will drain the wakif property even if he has passed away. The purpose of this research is to examine how verses of the Qur'an interpret the implementation of productive Waqf to the welfare of the community. This research uses library research and content analysis methods by interpreting Qur'an verses related to Waqf, and none of the Verses of the Qur'an explicitly mention the word waqf. Waqf's management and supervision are carried out to the maximum so that the assets that have been converted can be empowered and useful in general so that the whole community can feel the Waqf results. The productive and innovative way of managing Waqf and intensive supervision will make the mauquf alaih economically independent, educational, health, religious. Keywords: Indonesian Waqf Board, Productive Waqf, Waqf